Genome editing iPSC to purposing enhancement of induce CD8 killer T cell function for regenerative immunotherapy - Sota Kurihara; Akihiro Ishikawa; Shin Kaneko (BMC, 2024)
Abstract In recent years, immunotherapy has become a standard cancer therapy, joining surgery, chemotherapy, and radiation therapy. This therapeutic approach involves the use of patient-derived antigen-specific T cells or genetically modified T cells engineered with chimeric antigen receptors (CAR) or T cell receptors (TCR) that specifically target cancer antigens. However, T cells require ex vivo stimulation for proliferation when used in therapy, and the resulting "exhaustion," which is characterized by a diminished proliferation capacity and anti-tumor activity, poses a significant challenge. As a solution, we reported "rejuvenated" CD8 + T cells that possess high proliferation capacity from induced pluripotent stem cells (iPSCs) in 2013. This review discusses the status and future developments in immunotherapy using iPSC-derived T cells, drawing insights from our research to overcome the exhaustion associated with antigen-specific T cell therapy.